Long-term corrosion protection of styrene acrylic coatings enhanced by fluorine and nitrogen co-doped graphene oxide. (13th December 2021) - An, Haoran; Gao, Yanan; Wang, Shengyuan; Liang, Shuang; Wang, Xin; Li, Na; Sun, Zhanying; Xiao, Jijun; Zhao, Xiongyan
Abstract: Graphene materials are widely used as a physical barrier when applying anticorrosion polymer coatings due to their large surface area and layered structure. However, the electrical conductivity of intrinsic graphene can accelerate galvanic corrosion and shorten the protection period. In this work, fluorine and nitrogen co-doped graphene oxide (FNGO) was synthesized by a hydrothermal process and acted as an anticorrosion filler in waterborne styrene acrylic coatings. Styrene acrylic coatings with 0.4 wt% FNGO showed a corrosion current density that was two orders of magnitude lower than the other samples in the potential polarization test and the largest impedance modulus in the electrochemical impedance spectroscopy results. The outstanding corrosion protection was attributed to the graphene acting as a physical barrier and the synergistic effect of the doped fluorine and nitrogen. In addition to the 'labyrinth effect' of the graphene matrix, the nitrogen atoms inserted in the graphene plane and fluorine atoms grafted on the graphene simultaneously adjusted the electrical properties of graphene, prohibiting electron transport between it and the styrene acrylic resin matrix. This result indicates that doped graphene oxide has great potential to increase the corrosion resistance of waterborne coatings.